A Landscape Approach to Reconstructing Territorial Mobility during the Parkhill Phase in Southern Michigan and Ontario. (2nd October 2017) - Carr, Dillon H.
ABSTRACT: Territorial mobility during the Middle Paleoindian period is estimated by calculating distance to source for the primary toolstone on Parkhill phase sites in the lower Great Lakes region. Estimates of territorial mobility are compared to ethnographic data from subarctic caribou hunting societies suggesting that the geographic distribution of lithic toolstone during the Parkhill phase is at a scale similar to that of a single-tiered network of local forager communities (i.e., minimal bands).